Motivasi Petani dalam Pemanfaatan Limbah Ternak sebagai Pupuk Organik di Kabupaten Karanganyar - Ardela Nurmastiti; Ratih Setyowati; Zulfa Nur Auliatun Nissa (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Indonesia is primarily an agricultural country with a wealth of natural resources, making agriculture one of the most significant foundations of the nation's economy. One initiative in agricultural growth is organic farming. Organic farming requires that chemical compounds not pollute the land used and have good accessibility. One of the efforts to prevent agricultural and environmental pollution is to use organic fertilizers. Organic fertilizers are obtained from the utilization of livestock waste. Farmers still do not fully use organic fertilizers in their farming. So, motivation is needed to encourage farmers to utilize livestock waste as organic fertilizer. This study aimed to investigate the elements that affect farmer motivation, the extent to which farmers are motivated to use animal waste, and the variables that affect farmers' motivation to use livestock waste as organic fertilizer. The sample data collection technique was purposive. As many as 77 farmer respondents used livestock waste. Multiple linear regression analysis is employed in this study's quantitative descriptive methodology to examine the elements that influence farmers' decisions to use animal manure. The study's findings indicate that while non-formal education falls into the high category, internal criteria like age, experience, and formal education fall into the moderate category. External elements are categorized in the high category and consist of capital accessibility, infrastructure accessibility, and counseling intensity. Farmers' motivation to use animal manure is another indicator of their high level of motivation. Age, formal education, and non-formal education are internal factors that have no impact on farmers' inclination to use animal waste; nevertheless, farming experience has an impact. Farmers' willingness to use livestock waste is influenced by external factors such as the accessibility of capital, the quality of infrastructure, and the level of counseling.